PENGAWASAN LALU LINTAS DALAM MENGATASI KEMACETAN OLEH DINAS PERHUBUNGAN DI KOTA PEKANBARU TAHUN 2016 - Novrisaldi Nasution; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Town of Pekanbaru in this time represent as town which is flange to Townof metropolitandengan various accessing development and also facility whichprogressively expand. It is of course the mentioned will add the amount of residentresiding in in Town of Pekanbaru, as according to Vision Mission Town ofPekanbaru in this time [is] to " Realizing Town of Pekanbaru as Metropolitan Townwhich is Madani". To be metropolitan Into The City Government of Town ofPekanbaru expected can and listen carefully in executing action to prevent toordinary problems happened in Metropolitan Town that is one of them is " Jam".phenomenon which is writer find field, that is less him form observation executedby On Duty Communication of Town of Pekanbaru in overcoming problems oftraffic jam in Town of Pekanbaru. This Matter because of still there are some jamlocation dot which not yet got observation at the (time) of the happening of jamwhich ought to get observation by On Duty Communication of Town of Pekanbaruas party/ side in charge of. Therefore observation ought to done/conducted by OnDuty Communication of Town of Pekanbaru shall be coherent done/conductedroutine and also at its execution, because otherwise of course this matter will stillgoing on and progressively increase location becoming jam gristle dot in Town ofPekanbaru.This research is executed in Februari 2017 till April 2018. Intention of thisresearch is to know form observation of traffic executed by On DutyCommunication of Town of Pekanbaru in overcoming jam. Method which is usedin this research is descriptive method qualitative, where this research of researchertry to explain observation form executed by On Duty Communication Of Town ofPekanbaru. Technique data collecting in this research is to use technique interviewand documentation. Pursuant to interview to all informan and pursuant tosupporter data and also information obtained by researcher whendoing/conducting research, can be concluded that observation form executed by OnDuty Communication of Town of Pekanbaru do not walk better. because manyresistor fakor so that the observation do not walk maximallyKeyword: Observation, Traffic, On duty Communication